Fourth Hankel determinant for a subclass of close-to-convex function and its verification / Badrul Amin Jaafar, Muhammad Aslam Mohamad and Nur Hakimah Husin - Jaafar, Badrul Amin; Mohamad, Muhammad Aslam; Husin, Nur Hakimah (2019)
Complex analysis involves studying the properties of complex number function. Geometric function theory is one of the branches of complex analysis field. A new class of function is often introduced and it is common for researchers to find its properties. However. it is difficult for researchers to generalized existing subclasses of analytic functions with limited stud¬ ies and inadequate sources of references on Hankel determinants. If a new class of function is successfully defined, then some of its properties discussed.